ISCHEMIC STROKE IN CHILDREN WITH SPONTANEOUS DISSECTION OF INTRACRANIAL ARTERIES - L.A. Kalashnikova; L.A. Dobrynina; R.N. Konovalov; M.V. Korotenkova ("Paediatrician" Publishers LLC, 2009)
Authors give a description of spontaneous dissection (SD) of extra- and intracranial arteries in 5 children (4 boys and 1 girl) in age 5-15 years old. SD in 4 children was developed as ischemic stroke, and in 1 patient - as transitory ischemic attack. SD was provoked by alcoholic beverage, movement of head, straining effort at defecation. Magnetic resonance angiography in acute period and in 1.5 months and later allowed restoration of partial and complete arterial permeability. Magnetic resonance imaging in all patients showed infarction in basin of affected arteries. Clinical and laboratory signs of thrombophilia were absent. Authors made a conclusion, that diagnosis of SD is based on complex evaluation of clinical sign and repeated angiography data. Differentiation is carried out between SD and thrombosis of intracranial arteries. Key words: children, spontaneous intracranial dissection, ischemic stroke. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):142-146)